Potter's hands a therapeutic pottery art comples in Calumpit, Bulacan for the young fighters of abuse - Dalao, Miguel M.; Navarra, Nappy L. (Quezon City College of Architecture, University of the Philippines Diliman, 2018)
With the increasing cases of physical, sexual, emotional child abuse and neglect in the Philippines, it is deemed that the government facilities are not sufficient enough to cater to the number of child abuse cases in the Philippines, which is why NGOs have created their own facilities and collaborate with the government in order to aid with the insufficient therapy programs. Along with this problem is the decline of pottery in Calumpit, Bulacan, which is recognized to be the "Pottery Country of the Philippines", wherein the pottery businesses in the municipality slowly lose its impact to people and to the market and struggled to deal with the modernization and lose of interest of today's generation. Integrating the two issues involving the need of supplementary childcare facilities and therapeutic programs and the diminishing of pottery culture and industry, this study introduces pottery along with its psychotherapeutic effects, as a new type of program that can incorporate both art therapy and cognitive behavior therapy to nurture the child's development. Through landscape planning and design, the study presents a therapeutic pottery art complex that corresponds to the needs of the young fighters of abuse. This study will be a significant endeavor in helping the community of young fighters of abuse as well as the community of Calumpit with respect to its pottery industry.
Includes appendices
Thesis (Bachelor of Landscape Architecture) -- University of the Philippines Diliman
Keywords: Pottery; Recreational therapy; Child psychotherapy